Evidence that the anxiolytic-like effects of chlordiazepoxide on the elevated plus maze are confounded by increases in locomotor activity. - Dawson, G; Crawford, S; Collinson, N; Iversen, S; Tricklebank, MD (1995)
In exploratory animal models of anxiety, such as the elevated plus maze, the anxiogenic- and anxiolytic-like effects of drugs may be confounded by changes in locomotor activity. In the present experiments, the sensitivity of several measures of anxiety and locomotor activity in the elevated plus maze were assessed. Both chlordiazepoxide hydrochloride (CDP, 7.5 mg/kg) and d-amphetamine sulphate (AMP, 0.75, 1.5 mg/kg) increased the percent time on the open arms and doses of 7.5 mg/kg and 1.5 mg/kg CDP and AMP, respectively, increased the number of entries into the open arms. The increase in these measures might suggest that both compounds induced an anxiolytic-like effect. Although FG 7142 (30.0 mg/kg) did not decrease the number of entries to the open arms, it did decrease the time on the open arms, which might suggest that it had anxiogenic-like effects. Similarly, buspirone reduced both the number of entries into the open arms and the time spent on the open arms. However, all the compounds significantly affected locomotor activity. CDP (3.0 and 7.5 mg/kg) increased the total number of arm entries, the distance travelled on the open arms and the mean speed of the animals on the open, and in the closed arms. Moreover, the distance travelled by the animals in the closed arms was increased by 1.0 mg/kg CDP, a dose that had no measurable effects on the indices of anxiety.(ABSTRACT TRUNCATED AT 250 WORDS)